2021
DOI: 10.1088/1361-6560/ac36a2
|View full text |Cite
|
Sign up to set email alerts
|

Fibro-CoSANet: pulmonary fibrosis prognosis prediction using a convolutional self attention network

Abstract: Idiopathic pulmonary fibrosis (IPF) is a restrictive interstitial lung disease that causes lung function decline by lung tissue scarring. Although lung function decline is assessed by the forced vital capacity (FVC), determining the accurate progression of IPF remains a challenge. To address this challenge, we proposed Fibro-CoSANet, a novel end-to-end multi-modal learning based approach, to predict the FVC decline. Fibro-CoSANet utilized computed tomography images and demographic information in convolutional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The type of classification system used in a BCI system is mostly determined by the application's nature and location. With the recent application of deep learning (DL) in different domain (Mashrur et al, 2019 , 2021a ; Nazi et al, 2021 ), Teo et al ( 2017 ) showed the subjects 3D virtual jewelry objects, asked to rate them on a Likert scale, and then categorized EEG signals using deep learning. Again, Aldayel et al ( 2020 ) emphasized the need of spectral valence features to improve prediction accuracy and the merging of classifiers using deep learning to extract features.…”
Section: Introductionmentioning
confidence: 99%
“…The type of classification system used in a BCI system is mostly determined by the application's nature and location. With the recent application of deep learning (DL) in different domain (Mashrur et al, 2019 , 2021a ; Nazi et al, 2021 ), Teo et al ( 2017 ) showed the subjects 3D virtual jewelry objects, asked to rate them on a Likert scale, and then categorized EEG signals using deep learning. Again, Aldayel et al ( 2020 ) emphasized the need of spectral valence features to improve prediction accuracy and the merging of classifiers using deep learning to extract features.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were run on the OSIC Pulmonary Fibrosis Progression Challenge Benchmark Dataset, 34 the most popular dataset to train models for predicting patients’ severity of decline in lung function. Fibro-CoSANet extracts visual features from CT scans also by means of an attention layer, and combines such features with other clinical data 32 . Then, the prediction of the FVC slope is performed by using regression.…”
Section: Ai Methods In Diagnosis and Prognosis Of Ildsmentioning
confidence: 99%
“…Researchers typically consider factors such as image complexity, edge conditions, and uncertainty. When selecting samples, priority is given to images containing crucial structures, lesion regions [22] , or regions that are difficult to segment [23] , as these samples are indispensable for enhancing the model's capability to adapt to intricate scenarios. Considering the specialized nature of the medical image segmentation task, those samples that are important in clinical practice can be selected by combining medical expertise [24] .…”
Section: The Information Selectionmentioning
confidence: 99%